Pengaruh Model Discovery Learning Terhadap Aktivitas dan Hasil Belajar Kognitif Peserta Didik - Werda Bariroh; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2019)
This study aims to determine the effect of discovery learning on activities and cognitive learning outcomes of class VIII students of SMPN 1 Pugung Tanggamus in